Faces da pandemia : entre assaltos do real e invenções de sentido - Salim, Anna Luiza Dantas (2023)
The pandemic of COVID-19 confronted speakingbeings in various parts of the world with the real of death and illness brought on by the SARS-CoV-2 virus, favoring the eruption of trauma and the exacerbation of anxiety. However, the unfolding of the real of the pandemic and its configuration as trauma or not will vary according to the different positions of the subjects, determined by fantasy, constitutive of psychic reality and the raw material of tales and dreams. The problem that guided the research was: in what way were the dimensions of trauma, anxiety and fantasy dealt with in the tales and dream reports produced during the COVID-19 pandemic? The overall goal of the research was to investigate how the dimensions of fantasy, anxiety and trauma present themselves in the literary writings about the COVID-19 pandemic present in the collections “20 tales about the pandemic” and “The Decameron Project: 29 stories of the pandemic” and in the dream accounts collected in “Confined Dreams”. The psychoanalytic method of research was used in the reading of the material, with the interpretation based on the primacy of the signifier and consideration of the real as beacons. In the tales readings, the importance of learning from the text and the short story`s characteristic of referring to questions that transcend the text itself were considered. Five stories and two dreams were selected for analysis. In the short story “Two sisters” the role of the familiar Other in defending against anxiety and trauma was highlighted. In the tale “47 seconds”, the exacerbation of anxiety in the contact with the other and the relationship between and different fantasies and misunderstandings in the context of the pandemic are staged. In the tale “Solstice of Hell” the role of fantasy in the defense against the real and the advent of trauma in severe illness due to the reliving of a traumatic mark is highlighted. In the tale “A gentle thief”, the helplessness of an elderly man in the pandemic and the role of his fantasy in the relationship with the health professional, whom he represents as a thief, are highlighted. In the tale “In the time of death, the death of time” the relationship of logical time with pandemic trauma is addressed. In the dreams analyzed, there is the unveiling of the object a and its anguishing effects, linked to the shaking of fantasy.We conclude by pointing out some elements about the pandemic of COVID19 that recur in the different short stories: the worsening of social denouement, tied to the gulfs between the fantasies of the different subjects regarding the pandemic, prevalence of the real dimension of the body of the other in the pandemic, experienced as a producer of anxiety, thickening of imaginary defenses, wish engender aggressiveness, role of the Other in dampening or favoring the irruption of trauma and anxiety during the pandemic and the role of fantasy in defense against the pandemic real.